Feminine figurine of Shengavit and its parallels - Azizyan, Anna (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
It is widely believed that anthropomorphic, especially feminine images are characteristic to early agricultural cultures. Unlike Mesopotamia, anthropomorphic statues are not very common in the Armenian Highlands. The present article discusses female figurines of Shengavit culture of Early Bronze Age with particular case from the settlement Shengavit. Our inquires demonstrate, that some feminine figurines are shaped in a generalized-realistic way, and some in a schematic-symbolic style. Feminine figurines have been found in dwellings, in hearthsand around them, sometimes also in ritual structures. They are mostly depicted nude. The female figurines were probably used during ritual ceremonies, which, apparently, took place around the hearths. During these ceremonies, the limbs of the figurines - arms and legs, sometimes the body and the head - were dismembered. Female statuettes with animal heads probably symbolized and at the same time attributed to the symbolic features of the animal. Female statues symbolized fertility and maternal deities, which were used in rituals.